The Effect of Service Quality and Product Excellence on Customer Satisfaction and Loyalty - Nugroho, Zahra Dini; Sukresna, I Made (International Journal of Economics Development Research (IJEDR), 2025)
The increasingly intense competition in the banking industry and shifts in customer behavior driven by rapid digitalization have made service quality and product excellence critical factors in maintaining customer satisfaction and loyalty. Bank Mandiri Semarang Pemuda Area, as a service unit with high transaction volumes and diverse customer characteristics, must ensure that its services and products consistently meet customer needs and expectations. This study aims to examine the influence of service quality and product excellence on customer loyalty, with customer satisfaction serving as a mediating variable. A quantitative approach with an explanatory research design was employed, involving active customers selected through purposive sampling. Data were analyzed using structural equation modeling with AMOS software. The findings indicate that service quality and product excellence positively influence customer satisfaction. While service quality does not directly affect customer loyalty, product excellence shows a direct positive relationship with loyalty. Customer satisfaction plays a key mediating role and emerges as the most important factor in strengthening customer loyalty. These results highlight the strategic importance of improving both service delivery and product attributes to enhance customer satisfaction, which in turn fosters long-term loyalty in the banking sector.